Analysis of Income From Rice Farming Business in Tanjung Morawa District, Deli Serdang Regency - Dian Dominika br Ginting; Retna Astuti Kuswardani; Endang Sari Simanullang; Muhammad Reza Aulia (Dinasti Publisher, 2025)
Lowland rice farming is the main source of income for farmers in rural Indonesia and plays a strategic role in national food security. However, structural challenges such as high production costs, fluctuations in grain prices, and limited access to modern agricultural technology still limit improvements in farmer welfare. This study aims to analyze the level of income and cost efficiency of lowland rice farming in Tanjung Morawa District, Deli Serdang Regency. Using a quantitative descriptive approach through a case study design, primary data were collected from 46 farmers selected purposively, supported by secondary data from related agencies. Analysis techniques include calculating fixed and variable costs, revenues, and net income, complemented by an analysis of the business efficiency ratio using the Revenue/Cost (R/C) indicator. The results of the study indicate that rice farming in this area provides significant economic benefits with adequate cost efficiency, although labor and production input components are dominant burdens. These findings emphasize the importance of optimizing the allocation of production inputs and utilizing efficient agricultural technology as a strategy to increase farmer income. The main contribution of this study is to provide a relevant empirical basis for regional agricultural policy making and encourage the adoption of a data-based approach in evaluating the economic feasibility of sustainable rice farming.